A Theory of Assurance: Balancing Costly Formal Control with Tone at the Top - Penno, Mark (Management Science, 2022)
Informal tone at the top (TATT) is widely regarded as a fundamental ingredient of organizational control, yet because of its soft nature, the scholarship on TATT has not emphasized mathematical modeling. Observing that TATT refers to the example set by top management, I model TATT as, ceteris paribus, reflecting the expectation that the chief executive officer (CEO) will not divert organizational resources for personal benefit. The setting assumes that CEOs are randomly drawn from a labor pool containing candidates who either value career prospects (high type) or who do not value career prospects (low type). The fear of dismissal and a damaged career mean that high types tend to be less opportunistic than low types, who divert for personal gain. Contrary to the belief that trust and vulnerability go hand in hand, I identify conditions where TATT and optimal costly formal controls are complements. But I also show in the same setting that TATT and optimal formal controls can be substitutes. The results also explain why high levels of TATT may not be welcomed by the external auditor or certain stakeholders and explain ambiguous Sarbanes-Oxley reports. This paper was accepted by Suraj Srinivasan, accounting.